Comparative Study of Endothelial Function and Uterine Artery Doppler Velocimetry between Pregnant Women with or without Preeclampsia Development. (19th July 2012) - Brandão, Augusto Henriques Fulgêncio; Pereira, Ludmila Maria Guimarães; Gonçalves, Alessandra Cristina de Oliveira; Reis, Zilma Silveira Nogueira; Leite, Henrique Vítor; Cabral, Antônio Carlos Vieira
Abstract : Background . Poor placentation and systemic endothelial dysfunction have been identified as main events in Preeclampsia (PE). The relationship and chronology of these phenomena are important if we are to understand the pathophysiological mechanisms underlying this major clinical problem. Objectives . To compare the evolution of placentation and endothelial function in normotensive and preeclamptic pregnancies. Patients and methods . In a prospective cohort study, 59 pregnant women with a high risk of developing PE were subjected to flow-mediated dilation (FMD) and to Doppler velocimetry of uterine arteries in order to obtain their Pulsatility Index (UtA-PI). The variations in the FMD and UtA-PI values, between 16 +0 and 19 +6 and 24 +0 and 27 +6 weeks of gestation, were compared, taking PE development into consideration. Results . Nine patients developed PE and the other 50 women remained normotensive. At 16 +0 to 19 +6 weeks of pregnancy, patients that developed PE presented higher values of UtA-PI than the normotensive group, but there was no difference in FMD results between them. At 24 +0 to 27 +6 weeks, the patients that developed PE presented higher values of UtA-PI and lower values of FMD than the women that remained normotensive. Conclusions . These results corroborate the evidence that endothelial injury is secondary to poor placentation.